SCN1A-Related Epilepsy: Novel Mutations and Rare Phenotypes - Ma, Rui; Duan, Yiran; Zhang, Liping; Qi, Xiaohong; Zhang, Lu; Pan, Sipei; Gao, Lehong; Wang, Chaodong; Wang, Yuping (Frontiers in Molecular Neuroscience, 2022)
Objectives To expand the genotypes and phenotypes of sodium voltage-gated channel alpha subunit 1 (SCN1A)-related epilepsy. Methods We retrospectively collected the clinical and genetic information of 22 epilepsy patients (10 males, 12 females; mean: 9.2 ± 3.9 years; 3.9–20.3 years) carrying 22 variants of SCN1A. SCN1A mutations were identified by next-generation sequencing. Results Twenty-two variants were identified, among which 12 have not yet been reported. The median age at seizure onset was 6 months. Sixteen patients were diagnosed with Dravet syndrome (DS), two with genetic epilepsy with febrile seizures plus [one evolved into benign epilepsy with centrotemporal spikes (BECTS)], one with focal epilepsy, one with atypical childhood epilepsy with centrotemporal spikes (ABECTS) and two with unclassified epilepsy. Fourteen patients showed a global developmental delay/intellectual disability (GDD/ID). Slow background activities were observed in one patient and epileptiform discharges were observed in 11 patients during the interictal phase. Significance This study enriches the genotypes and phenotypes of SCN1A-related epilepsy. The clinical characteristics of patients with 12 previously unreported variants were described.